miR-29c increases protein synthesis in skeletal muscle independently of AKT/mTOR - Alves, Paula; Cruz, André; Silva, William J.; Labeit, Siegfried; Moriscot, Anselmo Sigari (International journal of molecular sciences, 2022)
microRNAs negatively regulate gene expression by blocking translation or increasing mRNA degradation. In skeletal muscle, these molecules play important roles in adaptive responses, and ongoing investigations are necessary to understand the fine-tune regulation of skeletal muscle mass. Herein we showed that skeletal muscle overexpression of miR-29c increased fiber size and force at 7 and 30 days after electrotransfer. At both time points, AKT/mTOR pathway components were downregulated, and, surprisingly, overall protein synthesis was strongly elevated at day 7, which normalized by day 30 after pCMVmiR-29c electrotransfer. These results indicate that miR-29c expression induces skeletal muscle hypertrophy and gain of function, which involves increased overall protein synthesis in spite of the deactivation of the AKT/mTOR pathway.